Reducing illegal immigration in Malawi: border control challenges and solutions - Kaisi, Sherrif Abobakar; Mohd Adnan, Normala; Aminudin, Rabi'ah (IIUM Press, 2024)
Illegal immigration presents a growing challenge for Malawi, undermining national security, straining resources, and exposing socio-political vulnerabilities. This qualitative study investigates the systemic challenges contributing to the inefficacies of border control, with a focus on the Immigration Department's management. Using in-depth interviews with key informants from the Immigration Department, Police Service, local government, and human rights organisations, the study identifies critical barriers, including insufficient funding, inadequate staffing, outdated policies, lack of advanced technological tools, and corruption. These systemic issues are exacerbated by Malawi's geographical vulnerability, with porous borders facilitating unauthorised migration, particularly from East Africa and the Horn of Africa. Grounded in the Collaborative Governance Framework, this research explores how multi-stakeholder collaboration can enhance border management effectiveness. The study underscores the urgent need for institutional reforms, increased resource allocation, capacity building, and inter-agency coordination